Realization of Personalized Services for Intelligent Residential Space based on User Identification Method using Sequential Walking Footprints - Jin-Woo Jung; Dae-Jin Kim; Z. Zenn Bien (Journal of Systemics, Cybernetics and Informatics, 2005)

(untitled)
A new human-friendly assistive home environment, Intelligent Sweet Home (ISH), developed at KAIST, Korea for testing advanced concepts for independent living of the elderly/the physically handicapped. The concept of ISH is to consider the home itself as an intelligent robot. ISH always checks the intention or health status of the resident. Therefore, ISH can do actively the most proper services considering the resident's life-style by the detected intention or emergency information. But, when there are more than two residents, ISH cannot consider the residents' characteristics or tastes if ISH cannot identify who he/she is before. To realize a personalized service system in the intelligent residential space like ISH, we deal with a human-friendly user identification method for ubiquitous computing environment, specially focused on dynamic human footprint recognition. And then, we address some case studies of personalized services that have been experienced by Human-friendly Welfare Robot System research center, KAIST.